Modeling decisions for artificial intelligence : 11th International Conference, MDAI 2014, Tokyo, Japan, October 29-31, 2014. Proceedings - Narukawa, Yasuo; Endo, Yasunori; Torra, Vicenc (Lecture Notes in Computer Science, 2014)
This book constitutes the proceedings of the 11th International Conference on Modeling Decisions for Artificial Intelligence, MDAI 2014, held in Tokyo, Japan, in October 2014. The 19 revised full papers presented together with an invited paper were carefully reviewed and selected from 38 submissions. They deal with the theory and tools for modeling decisions, as well as applications that encompass decision making processes and information fusion techniques and are organized in topical sections on aggregation operators and decision making, optimization, clustering and similarity, and data mining and data privacy.